2019
DOI: 10.1101/687400
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Impact of Měnglà virus proteins on human and bat innate immune pathways

Abstract: AbstractMěnglà virus (MLAV), identified in Rousettus bats, is a phylogenetically distinct member of the family Filoviridae. Because filoviruses Ebola virus (EBOV) and Marburg virus (MARV) modulate host innate immune pathways, MLAV VP35, VP40 and VP24 proteins were compared with their EBOV and MARV homologs for innate immune pathway modulation. In human and Rousettus cells, MLAV VP35 behaved like EB… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
1
1

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 64 publications
(102 reference statements)
0
2
0
Order By: Relevance
“…Using an IFN-β promoter assay, we showed that N has a role in suppressing IFN signaling pathway when stimulated by Sendai virus (SeV) infection ( Figure 5G ). N WT can inhibit IFN-β promoter activity, although not as well as Měnglà virus (MLAV) VP35, a potent inhibitor of IFN signaling (Williams et al, 2020). Both N Narm-NTD-LKR and N NTD show modest inhibition at the highest concentration tested.…”
Section: Resultsmentioning
confidence: 99%
“…Using an IFN-β promoter assay, we showed that N has a role in suppressing IFN signaling pathway when stimulated by Sendai virus (SeV) infection ( Figure 5G ). N WT can inhibit IFN-β promoter activity, although not as well as Měnglà virus (MLAV) VP35, a potent inhibitor of IFN signaling (Williams et al, 2020). Both N Narm-NTD-LKR and N NTD show modest inhibition at the highest concentration tested.…”
Section: Resultsmentioning
confidence: 99%
“…Using an IFNb promoter reporter assay, we showed that N has a role in suppressing IFN signaling pathway when stimulated by Sendai virus (SeV) infection (Figure 5G). N WT can inhibit IFNb promoter activity, although not as well as M englà virus (MLAV) VP35, a potent inhibitor of IFN signaling (Williams et al, 2020). Both N Narm-NTD-LKR and N NTD show modest inhibition at the highest concentration tested.…”
Section: Ll Open Access Iscience Articlementioning
confidence: 96%